1995
DOI: 10.1126/science.269.5220.60
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Water Radon Anomaly Before the Kobe Earthquake in Japan

Abstract: Radon concentration in ground water increased for several months before the 1995 southern Hyogo Prefecture (Kobe) earthquake on 17 January 1995. From late October 1994, the beginning of the observation, to the end of December 1994, radon concentration increased about fourfold. On 8 January, 9 days before the earthquake, the radon concentration reached a peak of more than 10 times that at the beginning of the observation, before starting to decrease. These radon changes are likely to be precursory phenomena of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
212
1
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(220 citation statements)
references
References 7 publications
4
212
1
3
Order By: Relevance
“…In some countries, the radiation dose to man caused by inhaled radon daughters constitutes more then 50% of the total dose [3,7]. The groundwater radon concentration is expected to reflect not radon concentration is expected to reflect not only in chemical form but also in structural properties of rock in an aquifer [8]. The radon concentration in groundwater is basically proportional to uranium concentration in adjacent rocks and soil in an aquifer, hydrothermal solution and with variations in stress in rocks associated with seismicity and also is usually higher than surface water.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, the radiation dose to man caused by inhaled radon daughters constitutes more then 50% of the total dose [3,7]. The groundwater radon concentration is expected to reflect not radon concentration is expected to reflect not only in chemical form but also in structural properties of rock in an aquifer [8]. The radon concentration in groundwater is basically proportional to uranium concentration in adjacent rocks and soil in an aquifer, hydrothermal solution and with variations in stress in rocks associated with seismicity and also is usually higher than surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Walia et al (2006) compiled radon time series interpreted as precursory signals for some major earthquakes having magnitude > 5, which occurred in N-W Himalayas. Igarashi et al (1995) interpreted precursory radon changes before the disastrous Kobe earthquake in Japan and this anomaly was particularly evident. Still more works should be dedicated to understand if certain delay between radon spikes and strong earthquakes is a time of preparation of those earthquakes, i.e., 40 up to 144 days before in a case history described by Einarsson et al (2008) in the South Iceland seismic zone, whereas Jaishi et al (2014) find a positive correlation between radon/thoron data and earthquakes soon after mainly, but sometimes are co-seismic.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, studies have shown useful data in the field of seismogeochemistry interpreted as geochemical precursory signals for impending earthquakes (Heinicke et al 1992;Igarashi et al 1995;Virk et al 2001;Steinitz et al 2003;Yang et al 2005Yang et al , 2006Zmazek et al 2005;Kumar et al 2009Kumar et al , 2015Walia et al 2009a;Fu et al 2015). Despite a full operative "earthquake prediction/early alarm" routine is still far to be accepted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most were the result of increases in river water flow, reservoir water levels, and water temperature, which occurred after the earthquake (Sato et al, 1995;King et al, 1995). In addition, several anomalous precursory changes were observed in groundwater (Tsunogai and Wakita, 1995;Igarashi et al, 1995; Kyoto University and the University of Tokyo, 1995). Many chemical and hydrological changes are reported to have occurred prior to large earthquakes in the past.…”
mentioning
confidence: 99%